APLIKASI E-COMMERCE PADA PT. PURNA KARYA MEDIKALINDO BENGKULU - Sri Handayani; Mesterjon Mesterjon; Indra Kanedi (Jurnal Media Infotama, 2014)
Has conducted research on the application of E-Commerce at. PT. Purna Karya Medikalindo Bengkulu. This study aims to provide solutions and help on how to make an e-commerce application system with php and mysql and market products online. Data were collected on March 28, 2014 in the form of product data and product images. The data is then processed into a source of discussion in this study. Besides the most important data is the procedure or mechanism of application of e-commerce itself is an act done after the purchase. The results of this study indicate that the need for an e-commerce application to be able to market and introduce products and the company to society at large and effective.Keyword: e-commerce, Marketing